Manajemen Media TV9: Telaah Perkembangan Bisnis Dakwah di Era Media Baru - Anggit Pamungkas; Umi Halwati (Dakwah Institut PTIQ Jakarta, 2023)
Da'wah of Islam using the media is a form of strategic application for Muslims regarding the need to spread Islamic teachings with a wider reach, so that it is hoped that it will be able to attract the interest of the general public to listen to the calls of Islamic teachings. Using media in da’wah is an innovative process in carrying out da'wah so that the